Effects of montmorillonite on the structure and properties of gelatin‐polyethylene glycol composite fibers. Issue 2 (27th November 2012) - Mu, Changdao; Li, Xinying; Guo, Jimin; Bi, Caixia; Li, Defu
Abstract To improve the thermal and mechanical properties of gelatin‐polyethylene glycol (PEG) composite fibers, montmorillonite (MMT) is incorporated into gelatin‐PEG composite fibers during gel‐spinning process. The effects of MMT on the structure and properties of gelatin‐PEG composite fibers are investigated. The viscosimetry analysis and transmission electron microscopy measurements show that MMT has a good dispersion in spinning solution at low loading, while serious aggregation is observed with excess amount of MMT adding. The data of X‐ray diffraction (XRD) show that MMT can be intercalated and exfoliated in gelatin‐PEG‐MMT nanocomposite fibers. Fourier transform infrared (FTIR) studies show the hydrogen bonding interactions between gelatin and MMT. The mechanical properties, differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) measurements indicate that the mechanical and thermal properties of nanocomposite fibers are improved as expected at low loading of MMT. However, excess amount of MMT decreases the mechanical and thermal properties of nanocomposite fibers due to poor dispersion and clay cluster induced gelatin chains aggregation. Moreover, it is found that the mechanical properties of gelatin‐PEG‐MMT nanocomposite fibers may be more sensitive to conformational change of gelatin molecules caused by the addition of MMT. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013